Transparasi Informasi Memoderasi Pengaruh Agresivitas Pajak Pada Nilai Perusahaan Pertambangan di Bursa Efek Indonesia - Ayu Aryista Dewi; Luh Gede Krisna Dewi (Department of Accounting-Faculty of Economic and Business (FEB), 2017)
The behavior of tax aggressiveness by taxpayers, especially corporate taxpayers will have an impact on the value of the company. The company's transparency to information relating to the company as well as the fulfillment of corporate liabilities to society, the environment, and government can also affect the value of the company. This research tries to dig deeply about the influence of tax aggressiveness undertaken by the company on the value of the company with the transparency of information as a moderating variable. This study also uses profitability control, leverage, firm size and audit quality. Tax aggressiveness is proxied by comparing Net Profit Margin to Net Profit Margin Industry. Company value is proxied with Tobins'Q ratio. The data selected by purposive sampling method. The sampel in this study were using 36 companies that listing in Indonesian Stock Exchange periode 2013-2015. The result of this research is tax aggressiveness have positive effect on firm value while transparency of information can strengthen the influence of tax aggressiveness on company value.